2018
DOI: 10.2147/cia.s156174
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training-induced gains in muscle strength, body composition, and functional capacity are attenuated in elderly women with sarcopenic obesity

Abstract: ObjectivesThe purpose of this study was to compare the effects of resistance training (RT) on body composition, muscle strength, and functional capacity in elderly women with and without sarcopenic obesity (SO).MethodsA total of 49 women (aged ≥60 years) were divided in two groups: without SO (non-SO, n=41) and with SO (n=8). Both groups performed a periodized RT program consisting of two weekly sessions for 16 weeks. All measures were assessed at baseline and postintervention, including anthropometry and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…In summary, our results suggest that the combination of HIIT and CIT induces a greater anti-obesity effect than HIIT alone, in a population of older obese adults, while maintaining muscle function. This is in line with the literature highlighting the importance of making efforts to promote healthy aging by consider both preventing obesity and maintaining or increasing skeletal muscle mass and function [51].…”
Section: Discussionsupporting
confidence: 89%
“…In summary, our results suggest that the combination of HIIT and CIT induces a greater anti-obesity effect than HIIT alone, in a population of older obese adults, while maintaining muscle function. This is in line with the literature highlighting the importance of making efforts to promote healthy aging by consider both preventing obesity and maintaining or increasing skeletal muscle mass and function [51].…”
Section: Discussionsupporting
confidence: 89%
“…Only RT as the sole treatment modality increased handgrip strength (+3.5 kg; p < 0.05 vs. all other groups). Similarly, improvement in strength, not in functional performance, was found in the small subgroup of women with SO in the RT treatment arm, in the study by de Olivera Silva et al, who also had a low frequency of exercise (2 session/week) [45]. On the contrary, Park et al [59] found that combined RT and AE training (5/week for 24 weeks) resulted in increased handgrip strength (+2.5 kg; p < 0.001 vs. baseline and vs. control) and walking speed (+0.15 m/s; p < 0.01 vs. baseline and vs. control).…”
Section: Treatment Of Sarcopenic Obesitymentioning
confidence: 85%
“…Both RT strategies similarly increased skeletal muscle mass vs. controls, but the 50-min sessions resulted in a significantly higher increase in strength and a modestly greater reduction in fat mass than the 30-min sessions [44]. Beneficial effects of RT were found in the study by de Oliveira Silva et al comparing non-sarcopenic with sarcopenic women with obesity; in the non-sarcopenic subgroup RT resulted in the amelioration of functional tests and strength as well as a reduction in fat mass compared to pre-training values [45]. Two additional studies evaluating aerobic exercise (AE) as the sole intervention fulfilled the inclusion criteria for the present review.…”
Section: Prevention Of Sarcopenic Obesitymentioning
confidence: 99%
“…It's believed that creatine supplementation has an effect on the increase in the activity of skeletal muscles (14,15). It has been suggested that creatine supplementation and resistance training improve properties of body composition (16,17). One possible reason for the increased lean body mass following creatine supplementation and strength training may be due to the increase in the number of satellite cells and muscle nuclear density in human skeletal muscle fibers (18).…”
Section: Discussionmentioning
confidence: 99%